Pengaruh Digital Financial Literacy Terhadap Perilaku Keuangan Masyarakat Kota Gresik - Karina Rakhma Pratitrasari; Indrawati Yuhertiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial literacy can be generally defined as a person's ability to understand, analyze, manage and communicate personal finances. Technological advances can have an impact on people's financial behavior. So financial literacy in this era of sophisticated digital technology and virtualization is very important for society, so digital financial literacy needs to be understood by the public. Digital financial literacy (DFL) is financial literacy in the form of digital financial technology. Demographic factors also influence financial behavior in society. Demographic factors can have an influence because the older you get, the more experience you have, including your financial intelligence, which also increases. This research used a sample of 125 respondents and obtained data from the results of a questionnaire distributed using the Likert scale assessment method. The analysis method uses structuralEquation Modeling Partial Least Square (SEM PLS) analysis. The results of this research conclude that Digital Financial Literacy (DFL) has been proven to have a good and significant effect on the financial behavior of the people of Gresik City. And educational demographics are proven to have a good and significant effect in moderating the influence of DFL on financial behavior.